Sci-tech analysis and related research on three glass beads unearthed from M686 in the Qin cemetery of Warring States Period in Hejia, Zhouling - Wenhui Ha; Feng Sun; Congwen Zhai (PLoS ONE, 2025)
This study presents a systematic analysis of three glass beads excavated from Tomb M686 in the Qin Cemetery of Warring States Period (475 BC-207 BC) in Hejia,Zhouling. The aim is to reveal their material characteristics and weathering mechanisms. Using super-depth-of-field 3D video microscopy system (OM), X-ray fluorescence spectroscopy (XRF), and micro-Raman spectroscopy (Raman), all three glass beads were identified as the unique lead-barium silicate glass system of ancient China. The primary coloring element in the glass is Cu(II), and the main weathering products include PbCO₃ and BaSO₄. Focusing mainly on the cross-section of Sample 2, scanning electron microscopy with energy dispersive spectroscopy (SEM-EDS) and X-ray photoelectron spectroscopy (XPS) were employed to investigate the microstructural and compositional changes. The results revealed continuous leaching of Pb, Ba, and S elements from the glass substrate during the weathering process, interacting with substances in the burial environment to form stable weathering products PbCO₃ and BaSO₄. Based on the analysis of elements in the buried environment soil, indicated that barium has higher water solubility than lead. The weathering process was also accompanied by the conversion of Cu(Ⅱ) to Cu(Ⅰ), which explains the color alteration associated with glass weathering. This research is the first to integrate multiple microscopic techniques to systematically explore the weathering processes of lead-barium glass from the Warring States period, elucidating both its coloring mechanism and the formation pathways of weathering minerals. The findings provide technical support and a theoretical foundation for the understanding and preservation of related cultural relics.